A Survey on Approaches to Solve Travelling Sa- lesman Problem - Prabakaran, S. (International Journal of Psychosocial Rehabilitation, 2020)
Travelling Salesman Problem (TSP) is widely used in traffic management and the transportation in- dustry where the route optimization would speed up services and increase efficiency. In this paper, we survey the most popular approaches including dynamic and meta-heuristic algorithms to solve the Travelling Salesman Prob- lem. Our survey clearly indicates that meta-heuristic algorithms like Ant Colony Optimisation (ACO) take addition- al time to arrive at the solution but returns the best optimal route when compared with others. Hence, we take our research forward in improving the ACO technique to support environmental changes like weather, traffic conges- tions and delays in real time and return the optimal route.